Categorized and mapping the lexical meaning that describing sexual harassment (oscenity / lewd) crimes in Malay tabloid press / Ain Nadhirah and Rozaimah Rashidin - Mohd Shah, Ain Nadhirah; Rashidin, Rozaimah (Universiti Teknologi MARA, 2021)
The categorization of meanings against lexical items that have multiple meanings or that undergo an expansion of meaning often poses problems to language users. This is because language users are often confused and unsure of the true meaning of a lexical item based on the context of its use. Studies on lexical semantics have been extensively conducted but most of the studies conducted focus on the meaning of adjectives, idioms and verbs only. Studies linking word meaning to sexual crime using newspaper data are still considered new and still lacking in number. This study, which uses Prototype Theory, will utilize digital newspaper data, namely Harian Metro, which is expected to fill the existing gaps. This prototype theory is proven to help unravel the cognitive processes involved as the reader tries to understand the true meaning of the word meaning that describes this obscene sexual crime. This study also proves that the use of cognitive semantics by utilizing prototype theory as well as the concept of lexical mapping has helped the process of utterance comprehension take place. All these cognitive processes are used in helping the reader understand the true meaning of a word. This study proves that the lexical used to describe the obscene crime is easily understood by the reader but there are other features that can be used by the author to describe the obscene sexual crime. This aims to further facilitate the reader's understanding of obscene sexual crimes. Overall, the results of this study found that the lexical used is appropriate to the concept of the crime of obscenity